ASPECTS REGARDING THE INTRODUCTION OF STATIC CONSTRUCTIONS, PYRAMIDS, IN THE PHYSICAL EDUCATION LESSON, AT PRIMARY SCHOOL - Dana Ioana CRISTEA; Anca Maria SABĂU; Aurelian Andrei CRISTEA; Emilia GROSU; Mihai Ionel ILLE (Editura Universităţii din Oradea, 2021)
Applying ACROGYM in the school and club permits a differentiated class in face of the challenges proposed, aligning theory and practice and teaching the students about certain concepts, procedures and attitudes the modality offers. It is also important for the proposals to be varied in opportunities and present different means for the practice, which can be developed by students with different physical builds, preserving the heterogeneity of the classes and favoring inclusion. The purpose of the paper is to provide models of static constructions - pyramids, which can be made with primary school students. Given the low degree of difficulty in building, these can also be practiced by students with special educational requirements, thus increasing the possibilities for physical exercise. Pyramids can be used successfully in sporting demonstrations in school or county competitions, dance, contemporary dance, show-dance, cheer-leading and so on, both as a starting position and as a final position.